2003
DOI: 10.1046/j.1365-8711.2003.06990.x
|View full text |Cite
|
Sign up to set email alerts
|

Black widow pulsars: the price of promiscuity

Abstract: The incidence of evaporating ‘black widow’ pulsars (BWPs) among all millisecond pulsars is far higher in globular clusters than in the field. This implies a special formation mechanism for them in clusters. Cluster millisecond pulsars in wide binaries with white dwarf companions exchange them for turnoff‐mass stars. These new companions eventually overflow their Roche lobes because of encounters and tides. The millisecond pulsars eject the overflowing gas from the binary, giving mass loss on the binary evoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…Indeed, the cluster gamma-ray flux appears to correlate with the expected MSP formation rate (Abdo et al 2010a). It had been noticed that a large fraction of the radio MSPs in globular clusters are tight, often evaporating, black-widow-type binaries and it was suggested that this was a true difference from the Galactic field population (King et al 2003). However, it now seems that this was largely an artifact of the very long radio dwell times used for cluster searches that allowed discovery of radio-intermittent MSPs generally undetectable to field surveys.…”
Section: Pulsar Population and The Millisecond Pulsar Revolutionmentioning
confidence: 99%
“…Indeed, the cluster gamma-ray flux appears to correlate with the expected MSP formation rate (Abdo et al 2010a). It had been noticed that a large fraction of the radio MSPs in globular clusters are tight, often evaporating, black-widow-type binaries and it was suggested that this was a true difference from the Galactic field population (King et al 2003). However, it now seems that this was largely an artifact of the very long radio dwell times used for cluster searches that allowed discovery of radio-intermittent MSPs generally undetectable to field surveys.…”
Section: Pulsar Population and The Millisecond Pulsar Revolutionmentioning
confidence: 99%
“…However, since the size of the eclipse depends on the inclination angle (King & Beer 2005), not all BWPs are expected to show eclipses. As suggested by King et al (2003), the formation of BWPs needs two phases: a first one in which the companion spins-up the NS to millisecond periods and a second where the companion is ablated by the pulsar. While it is difficult to describe the two phases using the same star as a companion to the MSP, in globular clusters (GCs), where encounters and exchange interactions are frequent, the white dwarf (WD) companion responsible for the pulsar spinning-up can be replaced by a main-sequence star via an exchange interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Such an overabundance is indicative of strongly enhanced dynamical activity in these dense stellar systems, which promotes the formation of a conspicuous number of exotic objects, such as blue straggler stars, X-ray binaries, cataclysmic variables, and MSPs (Bailyn 1992;Cool et al 1995;Ferraro et al 1995Ferraro et al , 2001aFerraro et al , 2015bGrindlay et al 2002;Pooley et al 2003;Ransom et al 2005), which can be used to probe the complex interplay between dynamics and stellar evolution (e.g., Goodman & Hut 1989;Hut et al 1992;Phinney 1992;Ferraro et al 2003bFerraro et al , 2009Ferraro et al , 2012Ferraro et al , 2015aPossenti et al 2003;Verbunt & Freire 2014). In this respect, the study of optical companions to binary MSPs in GCs is of the utmost importance, since it presents the opportunity to gain insights into the impact of dynamical interactions (which are particularly frequent in dense environments) on MSPs and stellar evolution, e.g., favoring binary formation (through tidal captures), binary shrinking (through fly-by), and consequent mass transfer activity, as well as exchange interactions that are able to substitute the original companion that recycled the pulsar, with a new, more or less perturbed, star (see, e.g., Rasio et al 2000;Ferraro et al 2003c;King et al 2003;Sabbi et al 2003aSabbi et al , 2003bBenacquista & Downing 2013;Mucciarelli et al 2013). Moreover, in the case of WD companions, it is possible to estimate the masses and cooling ages of the systems through direct comparison of their properties with stellar evolutionary models (see, e.g., Ferraro et al 2003a;Pallanca et al 2013b), while accurate mass measurements require spectroscopical techniques (e.g., van Kerkwijk et al 1996;Bassa et al 2006;Antoniadis et al 2012Anto...…”
Section: Introductionmentioning
confidence: 99%